These are three solutions
(0,-2)
(1,3)
(2,8)
We first add both 19.8 by 19.8 and therefore, that would give us 39.6.
42 - 39.6 = 2.4.
2.4 ÷ 2 = 1.2
1.2 would be the length of each sides.
The value of d from the given expression is 15
<h3>Word problem leading to equation</h3>
From the given statement the sum of five times d and five times five is a
hundred is interpreted as;
5d + 5(5) = 100
5d + 25 = 100
Subtract 25 from both sides
5d = 100 - 25
5d = 75
d =15
Hence the value of d from the given expression is 15
Learn more on word problem here: brainly.com/question/13818690
#SPJ1
❥![\Large\pmb{ \underline {\tt Answer}}](https://tex.z-dn.net/?f=%5CLarge%5Cpmb%7B%20%5Cunderline%20%7B%5Ctt%20Answer%7D%7D)
So we can only find x if other two angles of triangle is given.
In angle B as u can see boxed shape angle is there then it probably means it's a 90° angle.
We know sum of angles of triangle = 180°
{Reson :-
There's a formula to fund sum of angles of figure
- (n-2) × 180
- (3 -2) × 180
- 1 × 180
- 180°
}
Now Let's proceed
![\boxed{ \rm Side_1+Side_2+Side_3 = 180\degree}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Crm%20Side_1%2BSide_2%2BSide_3%20%3D%20180%5Cdegree%7D)
Fill all the given values
![\dashrightarrow \tt 90 \degree + 55 \degree + c = 180 \degree](https://tex.z-dn.net/?f=%20%5Cdashrightarrow%20%5Ctt%2090%20%5Cdegree%20%2B%2055%20%5Cdegree%20%2B%20c%20%3D%20180%20%5Cdegree)
![\\ \\](https://tex.z-dn.net/?f=%20%5C%5C%20%20%5C%5C%20)
![\dashrightarrow \tt 145\degree + c = 180 \degree](https://tex.z-dn.net/?f=%20%5Cdashrightarrow%20%5Ctt%20145%5Cdegree%20%2B%20c%20%3D%20180%20%5Cdegree)
![\\ \\](https://tex.z-dn.net/?f=%20%5C%5C%20%20%5C%5C%20)
![\dashrightarrow \tt c = 180 \degree - 145\degree](https://tex.z-dn.net/?f=%20%5Cdashrightarrow%20%5Ctt%20%20c%20%3D%20180%20%20%5Cdegree%20-%20145%5Cdegree)
![\\ \\](https://tex.z-dn.net/?f=%20%5C%5C%20%20%5C%5C%20)
![\dashrightarrow \tt c = 35\degree](https://tex.z-dn.net/?f=%20%5Cdashrightarrow%20%5Ctt%20%20c%20%3D%2035%5Cdegree)
![\\ \\](https://tex.z-dn.net/?f=%20%5C%5C%20%20%5C%5C%20)
Value of x = 35°
~BrainlyVIP ⸙
Solve for <em>x</em> when √(<em>x</em> ² - 4) = 1 :
√(<em>x</em> ² - 4) = 1
<em>x</em> ² - 4 = 1
<em>x</em> ² = 5
<em>x</em> = ±√5
We're looking at <em>x </em>≤ 0, so we take the negative square root, <em>x</em> = -√5.
This means <em>f</em> (-√5) = 1, or in terms of the inverse of <em>f</em>, we have <em>f</em> ⁻¹(1) = -√5.
Now apply the inverse function theorem:
If <em>f(a)</em> = <em>b</em>, then (<em>f</em> ⁻¹)'(<em>b</em>) = 1 / <em>f '(a)</em>.
We have
<em>f(x)</em> = √(<em>x</em> ² - 4) → <em>f '(x)</em> = <em>x</em> / √(<em>x</em> ² - 4)
So if <em>a</em> = -√5 and <em>b</em> = 1, we get
(<em>f</em> ⁻¹)'(1) = 1 / <em>f '</em> (-√5)
(<em>f</em> ⁻¹)'(1) = √((-√5)² - 4) / (-√5) = -1/√5
The sign must be negative; see the attached plot, and take note of the negatively-sloped tangent line to the inverse of <em>f</em> at <em>x</em> = 1.